Development of Learning Methods Based on Prophetic Pedagogics - Pratama, Anggi Restu (Universitas Muhammadiyah Surakarta, 2022)
The research method used in this research is library research where library research is an activity to collect materials related to this research from books, scientific journals, literatures and other publications that are worthy of being used as sources. for the research that will be studied by the author, by describing and describing the data through several expert opinions. This research is expected to provide comprehensive facts regarding the development of learning methods contained in prophetic pedagogy. Prophetic pedagogy is a way of educating children taught by the prophets. As Muslims, Prophet Muhammad SAW is an example for education today, especially teachers how he educates his wife, children, friends, and neighbors with humane and amazing education so as to produce human beings with noble character. However, the prophetic pedagogic-based method is still not widely touched by many teachers today. Many of the learning methods that he gave us as examples to be applied in education, considering that nowadays many students experience a moral crisis.